Kant’s Concept of Moral Autonomy as a Philosophical Justification of Party Autonomy - Prasetiyo, Eko Dwi (Badan Arbitrase Nasional Indonesia, 2025)
One of the important doctrines in international private law, especially in the field of contract law, is the party autonomy doctrine. Although it has gained enormous acceptance, there is still debate about the existence of the doctrine, as well as disagreements about the exact parameters, scope and boundaries of the doctrine. Kant's categorical imperative: